Impact of developed acidity in milk and subsequent neutralization on changes in physico-chemical properties and oxidative stability of khoa - choudhary, sonika; Arora, Sumit; Kumari, Anuradha; Narwal, Vikrant; Sharma, Vivek (Indian Journal of Dairy Science, 2016)
Khoa is a heat-desiccated milk product prepared by continuous heating, stirring and scrapping in an open pan. Effect of developed acidity and subsequent neutralization on physico-chemical attributes and oxidative stability of khoa were evaluated. Results indicated that development of acidity and subsequent neutralization of milk resulted in significant changes (p<0.05) in colour, tyrosine value, lactulose, HMF, furosine, induction period, FFA content and peroxide value.Â However, Fatty acid profile and mineral composition of khoa were not much affected by acidity and neutralization except butyric acid and sodium content.Â